The Sexual and Reproductive Health Context of an Internally Displaced Persons' Camp in Northeastern Nigeria: Narratives of Girls and Young Women - Marlow, Heather M.; Kunnuji, Michael; Esiet, Adenike; Bukoye, Funsho; Izugbara, Chimaraoke (Frontiers in Reproductive Health, 2022)
In humanitarian settings, ~35 million girls and young women of reproductive age (15–24) are in urgent need of sexual and reproductive health (SRH) information and services. Young women and girls in humanitarian contexts are particularly vulnerable to unwanted pregnancies, unsafe abortion, gender-based violence, and early and forced marriage. We sought to understand girls' and young women's experiences with unwanted pregnancy, abortion, contraception, sexually transmitted infections (STIs), gender-based violence (GBV), and forced marriage in an IDP camp in Northeastern Nigeria. We conducted 25 in-depth interviews with girls aged 15–19 (N = 13; 8 single and 5 married) and young women aged 20–24 (N = 12; 3 single and 9 married). All interviews were audiotaped, transcribed, translated, computer recorded and coded for analysis. The participants in our study fled from and witnessed violence to arrive in the IDP camp with little material support. Lack of necessities, especially food, has driven many to sex in exchange for goods or into forced marriages. This, in turn, leads to increased unwanted pregnancies and unsafe abortions. Participants had limited knowledge about contraception, and some information about SRH services available in the camp, but overall, knowledge and utilization of SRH services was low.